Fabrication and detection of tissue-engineered bones with bio-derived scaffolds in a rotating bioreactor. - Song, K; Yang, Z; Liu, T; Zhi, W; Li, X; Deng, L; Cui, Z; Ma, X (2006)
In order to explore the methods for commercialized bone tissue engineering, engineered bones should be cultivated in bioreactors to realize three-dimensional culture under well-defined culture conditions. In the present paper, osteoblasts isolated from the cranium of 1-month-old Zelanian rabbits were inoculated on to the BDBS (bio-derived bone scaffolds) to investigate the three-dimensional fabrication of engineered bone in an RWVB (rotating-wall vessel bioreactor). The osteoblasts, after being transfected with green fluorescent protein, were respectively seeded at 2 x 10(6) and 1 x 10(6) cells x ml(-1) on to the BDBS and then cultured in a T-flask and an RWVB for 1 week. The morphologies and structure of the fabricated bone were investigated by using an inverted microscope, a scanning electron microscope and a laser confocal microscope using the stains haematoxylin/eosin and Toluidine Blue. After being digested from the scaffolds, the cells were assayed with ALP (alkaline phosphatase) stain, von-Kossa staining on mineralized nodules, type I collagen and bone morphogenetic protein-2 expression, and the cell expansion and growth curves using different culture methods were quantitatively determined with MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide). Furthermore, cell cycle and apoptosis were detected by using a flow cytometer, and total DNA was also assayed. For a comparative study, cell-seeded constructs were also cultured under static conditions. The results show that the cell number cultured in the RWVB was five times that in the T-flask. Bone tissues cultured in the RWVB with two different densities grew well, and the osteoblasts maintained their normal cycle and DNA content. The result demonstrates that, with the stress stimulation in the fluid in the RWVB, the active expression of ALP can be increased, rapid proliferation and differentiation of osteoblasts are possible and the three-dimensional fabrication of engineered bone could be realized.